PHYSICAL QUALITY OF BUFFALO MEAT MARINATED IN LIQUID SMOKE AND CITRIC ACID WITH DIFFERENT CONCENTRATION - Endah Purnamasari; Rifni Putri; Jully Handoko (Universitas Riau, 2013)
The purpose of this research was to evaluate the effect of combinated liquid smoke and citric acidwith different concentration on the physical quality namely pH value, cooking losses, water holding capacityand sensory characteristics. The method used in this research was Completely Randomized Design with 3 x 3factorial and three replications. The first factor was concentration of liquid smoke (0%, 1%, and 3%) and thesecond factor was citric acid (0%, 3% and 6%). The results indicated that buffalo meat sub merged in thecombinated liquid smoke and citric acid significantly affected (P<0,01) the pH value, water holding capacityand sensory characterictics but did not significantly (P>0.05) the cooking losses. Concentration ofcombinated liquid smoke 3% and citric acid 3% can increased water holding capacity, and soaling in theconcentration citric acid 6% gave the best sensory characteristics.Key words: buffalo meat, liquid smoke, citric acid.